2016
DOI: 10.1186/s12936-016-1320-8
|View full text |Cite
|
Sign up to set email alerts
|

Where chloroquine still works: the genetic make-up and susceptibility of Plasmodium vivax to chloroquine plus primaquine in Bhutan

Abstract: BackgroundBhutan has made substantial progress in reducing malaria incidence. The national guidelines recommend chloroquine (CQ) and primaquine (PQ) for radical cure of uncomplicated Plasmodium vivax, but the local efficacy has not been assessed. The impact of cases imported from India on the genetic make-up of the local vivax populations is currently unknown.MethodsPatients over 4 years of age with uncomplicated P. vivax mono-infection were enrolled into a clinical efficacy study and molecular survey. Study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
(49 reference statements)
2
22
0
1
Order By: Relevance
“…30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka. 74,75 Polyclonal infections are common in malariaendemic areas of different countries for both species and can arise from a single mosquito bite carrying multiple clones or from inoculation by different mosquitoes carrying single clones.…”
Section: Discussionsupporting
confidence: 81%
“…30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka. 74,75 Polyclonal infections are common in malariaendemic areas of different countries for both species and can arise from a single mosquito bite carrying multiple clones or from inoculation by different mosquitoes carrying single clones.…”
Section: Discussionsupporting
confidence: 81%
“…Cumulative data from different endemic settings indicates that transmission intensity and geographical isolation are important determinants shaping diversity and structure in P . vivax populations [23, 4253]. In this respect, the trends observed here infer that the K 1 sub-population may reflect a low intensity and moderately isolated reservoir of infection.…”
Section: Discussionmentioning
confidence: 68%
“…In the K 2 sub-population, a moderately high I A S of 0.2 was observed, with no evidence of epidemic transmission dynamics. Relative to other studies applying the same markers, the K 2 sub-population was most comparable to the meso-endemic setting of West Timor ( I A S = 0.19) [50], and to Bhutan ( I A S = 0.16) [53]. Over 60% of the infections in the Bhutanese study were imported from India, but epidemiological and molecular evidence of local transmission was also demonstrated; the resulting LD was postulated to reflect the composite of local inbreeding and imported infection transmission dynamics.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our results show that the historically oldest antimalarial substance (QN) has the greatest anti-cancer activity on dimerization. The effectiveness of these dimeric compounds in cancer models suggests that they should be investigated in other disorders where CQ has shown efficacy, including rheumatoid arthritis (33), malaria (34), prion disease (35) and viral disorders (36). …”
Section: Discussionmentioning
confidence: 99%